Timed Petri-net based formulation and an algorithm for the optimal scheduling of batch plants - Gu, Tianlong; Bahri, Parisa A.; Cai, Guoyong (Zielona Góra: Uniwersytet Zielonogórski)
The effective scheduling of operations in batch plants has a great potential for high economic returns, in which the formulation and an optimal solution algorithm are the main issues of study. Petri nets have proven to be a promising technique for solving many difficult problems associated with the modelling, formal analysis, design and coordination control of discrete-event systems.
Keywords: timed Petri nets; scheduling; batch plants; discrete event; algorithm; heuristics